Correlation of Serum Parathyroid Hormone with Hemoglobin Levels among Patients Undergoing Maintenance Hemodialysis - Numan Javed, Shahzad Shokat, Fazl-E-Mateen, Salwa Al-Ajam Azhar, Faisal Bashir, Faiz Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anemia is a common complication in chronic kidney disease which is associated with a reduced quality of life and an increase in morbidity and mortality along with high financial burden. Objective: To assess the correlation of serum intact parathyroid hormone with hemoglobin levels among patients undergoing maintenance hemodialysis. Methodology: This cross-sectional study was conducted at Dialysis Unit, Jinnah Hospital/Allama lqbal Medical College Lahore from 1st December 2022 to 30th June 2023. Sixty patients undergoing maintenance hemodialysis were enrolled. All patients underwent venepuncture by taking 3 ml of the blood using aseptic measures and sample was sent to pathology for the estimation of serum parathyroid hormone and hemoglobin levels as per manufacturer’s guidelines. Results: There were 60% males and diabetes was present in 40% patients. The mean age was 45.92±14.88 years, mean body mass index was 30.40±28.83 kg/m2, mean number of dialysis sessions was 2.53±0.50, mean serum parathyroid hormone was 605.56±390.30 and mean hemoglobin level was 7.72+2.05. Spearman rank correlation showed significant (P=0.046) correlation between serum parathyroid hormone and hemoglobin level. Conclusion: There was significant correlation was observed between serum intact parathyroid hormone with hemoglobin levels among patients undergoing maintenance hemodialysis. Keywords: Hemodialysis, Chromic kidney disease, Serum intact parathyroid hormone, Hemoglobin levels